The Application of Visual Communication Design Strategies in User Interface (UI) Experiences on Digital Platforms - Eriska, Marta (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Visual design influences an app's user-friendliness in digital applications-this study takes Shopee, Gojek, and Ruangguru MSN with their interfaces as examples Looking through these popular apps 'current visual strategies, it is hoped that readers will come to understand how user engagement quality impacts on other details. To get this insight a Qualitative descriptive approach has been used in which direct observation and interviews were held for ten active users coming from different regions. The result shows well-organized, simple layouts enable users to experience the features more convenient. Gojek received the most enthusiastic response thanks to its clear design and general ease of access to main functions. Shopee, although extremely visually rich, was often felt to be too busy due to a plethora of concurrent promotions and features. Ruangguru, on the other hand, conveyed a relaxed atmosphere helpful to learning activities. But certain parts needed to be improved in order to facilitate accessibility betterThe findings suggest that visual arrangements more in tune with users' daily habits can lead to better experiences for users. The emphasis on being clear and structurally coherent emerges as one of the most egg-packing features in delivering smooth, pleasing user experience.